Uso de extratos vegetais no controle in vitro do Colletotrichum gloeosporioides penz. Coletado em frutos de mamoeiro (Carica papaya L.) - Ferreira, Elzivan Felix; São José, Abel Rebouças; Bomfim, Marinês Pereira [UNESP]; Porto, John Silva; Jesus, Jailson Silva De (Sociedade Brasileira de Fruticultura, 2014)
Several alternatives have been studied and used in the control of plant diseases, in order to achieve the needs of producers and consumers desiring to reduce the use of pesticides. Thus, the objective of this study was evaluating the activity of plant extracts Azadirachta indica A Juss., Annona muricata L. and Lippia alba (Mill) N. E. Brown. in controlling of Colletotrichum gloeosporioides Penz. in vitro. The experiment was conducted in State University of Southwest Bahia, campus of Vitoria da Conquista city, State of Bahia, Brazil. Aqueous extracts of leaves of soursop leaves and lemongrass, and aqueous extracts of neem seeds and soursop were used to inhibit mycelial growth of pathogen of anthracnose from papaya fruits. The antifungal activity of the extracts was determined by measuring the mycelial growth of cutures. The experimental design was CRD in factorial (3x3x3) with four repetitions in both experiments. The results suggested inhibitory action of the leaf extract of lemongrass and the seed extract of soursop.

Diversas alternativas vêm sendo estudadas e utilizadas no controle de doenças de plantas, no intuito de suprir as necessidades dos produtores e consumidores no desejo de reduzir o uso de defensivos agrícolas. Assim, o objetivo deste trabalho foi avaliar a atividade de extratos vegetais de Azadirachta indica A. Juss., Anonna muricata L. e de Lippia alba (Mill) N. E. Brown. no controle de Colletotrichum gloeosporioides Penz. in vitro. O experimento foi conduzido na Universidade Estadual do Sudoeste da Bahia, Câmpus de Vitória da Conquista, Bahia, Brasil. Extratos aquosos de folhas de graviola e erva-cidreira, e extratos aquosos de sementes de nim e graviola foram usados visando à inibição do crescimento micelial do patógeno causador da antracnose em frutos de mamão. A atividade antifúngica dos extratos foi mensurada mediante a medição do crescimento micelial das culturas. O delineamento adotado foi o DIC em esquema fatorial (3x3x3), com quatro repetições, nos dois experimentos. Os resultados obtidos indicam maior inibição ao crescimento micelial do patógeno com o uso dos extratos de folhas de erva-cidreira e de sementes de graviola.
Use of plant extracts on control in vitro of Colletotrichum gloeosporioides penz. Collected in papaya fruits (Carica papaya L.)
Keywords: Controle alternativo; graviola; nim e erva-cidreira; Alternative control; soursop; neem and lemongrass